Sunken landscapes and settlement areas. On the reconquest of underwater archaeological sites - Cyril Dworsky (Internet Archaeology, 2023)
Prehistoric lake dwellings around the Alps have been of great interest to researchers and are now part of the UNESCO World Heritage List. These sites offer challenging but favourable building locations around a lake with constantly changing water levels, which likely resulted in a lot of movement from people and nature over time. When water levels rose, these sites were taken over by aquatic plants and animals. But owing to climate change, neozoa and neophytes are spreading quickly into new habitats. It is important to document and monitor these developments in order to understand the extent and potential threat of these species in different areas.